Evaluasi Kelayakan Air Sumur Di Kawasan Candi Muaro Jambi Berdasarkan Parameter Lingkungan Dan Kesehatan - Anggun Sarttika Erinza; Ardi Mustakim (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Well water is still one of the main sources of daily water supply for the residents of the Candi Muaro Jambi area. The dependence on well water makes it vital for consumption, cooking, and other domestic activities. However, with the increasing human activity, the development of tourist areas, and environmental changes in the surrounding area, the quality of the well water is at risk of being affected. This study aims to evaluate the feasibility of well water from an environmental and health perspective based on physical, chemical, and biological parameters, referring to the clean water quality standards set by the Ministry of Health of the Republic of Indonesia. The research employs a descriptive quantitative method, with well water samples taken from several points around the residential areas in the Candi Muaro Jambi region. The analyzed parameters include temperature, color, odor, turbidity, pH, nitrate content, metal content (Fe and Mn), and the presence of coliform bacteria. Laboratory test results show that most of the well water samples still meet the established physical and chemical standards, but some wells were found to have coliform levels exceeding the recommended threshold. This condition indicates contamination, most likely from domestic waste, particularly from household sanitation systems that are not ideally located relative to the wells. While the well water in the study area is generally still suitable for daily use, it is recommended that the community performs simple water treatment, such as boiling or filtration, before direct consumption. These measures are crucial to reduce contamination risks and ensure the water's quality for safe consumption and health.